2015
DOI: 10.1097/spv.0000000000000094
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Collagen Injection for Stress Urinary Incontinence in Women Proven by Transvaginal 3-Dimensional Ultrasound

Abstract: Although believed to be nondurable, CI was found to be objectively stable over time by transvaginal 3D US in a subset of women with durably improved SUI symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…We also studied our MPQ cohort in comparison with our previous long-term report on collagen which had data over 10 years. 8 While collagen had a retention rate of 87% from the first to last 3DUS, our current study has confirmed superior retention rates with MPQ, albeit at a mid-term follow-up.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…We also studied our MPQ cohort in comparison with our previous long-term report on collagen which had data over 10 years. 8 While collagen had a retention rate of 87% from the first to last 3DUS, our current study has confirmed superior retention rates with MPQ, albeit at a mid-term follow-up.…”
Section: Discussionsupporting
confidence: 68%
“…Our group has extensive experience with 3DUS, as we used this imaging technique to report on the durability of collagen over time in women treated for bothersome SUI who had a well-supported urethra and intrinsic sphincter deficiency (ISD). 8 In that study, we found that despite an overall volume retention rate of 84% at mean follow-up of 43 months, collagen significantly decreased in volume between the first and last follow-up visits.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Repeat synthetic MUS's after MUS complications were not favored by women who wished to avoid repeating a procedure that had already failed once and required removal. Furthermore, long‐term data on injectable agents supports better durability than initially reported …”
Section: Discussionsupporting
confidence: 52%
“…In this report, as we did for Collagen in the past ( 4 - 6 ), we examined our longer term experience with MPQ using subjective and objective (three-dimensional ultrasound (3DUS)) outcome criteria as well as studied factors that could predict success over time in order to better counsel patients with bothersome incontinence interested in a minimally invasive approach.…”
Section: Introductionmentioning
confidence: 99%